The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1161/01.str.29.9.1833
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Mitral Annulus Calcification and Carotid Atherosclerotic Disease

Abstract: Background and Purpose-It has been established that mitral annulus calcification (MAC) is an independent predictor of stroke, though a causative relationship was not proved, and that carotid artery atherosclerotic disease is also associated with stroke. The aim of this study was to determine whether there is an association between the presence of MAC and carotid artery atherosclerotic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
0
6

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 38 publications
9
67
0
6
Order By: Relevance
“…8,10) Consistent with the results of these 2 studies, we found a significant association between the presence of severe MAC and both carotid atheroma and stenosis > 60%. In the present The Wald value is equal to the "z statistic", which is used for testing the hypothesis of area.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…8,10) Consistent with the results of these 2 studies, we found a significant association between the presence of severe MAC and both carotid atheroma and stenosis > 60%. In the present The Wald value is equal to the "z statistic", which is used for testing the hypothesis of area.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, carotid artery atherosclerotic disease has been found with high prevalence in elderly patients with hypertension, hyperlipidemia, smoking, and DM. 13,14) The study of Adler, et al 8) was the first that showed a strong and significant association between the presence of MAC and carotid atherosclerosis. According to the results of their study, in the MAC group, MAC and age were the only independent predictors for carotid artery stenosis of ≥ 40%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8] Also, in recent studies, a close relationship has been established between MAC and carotid atherosclerosis (CAS) or coronary artery disease (CAD). [9][10][11] In view of these reports, it has been suggested that MAC is a manifestation of diffuse atherosclerosis of the vascular system. In patients with MAC, cardiovascular risk factors such as hypercholesterolemia, hypertension, and diabetes mellitus are also common, which lends further support to this hypothesis.…”
mentioning
confidence: 99%
“…While some investigators were finding that subjects with MAC had a higher prevalence of hypertension, diabetes, hyperlipidemia, increased BMI and smoking (31), others found no association between MAC, and diabetes and hyperlipidemia (32). Whereas, some researchers found significant relationships with CAD but not with smoking and gender (33). These differences with our study may be explained by (1) considerably younger population of our study than that seen in other studies, thus, some cardiac risk factors such as diabetes and hypercholesterolemia may not be overt at the time of study, (2) exclusion of patients from our study with renal failure, atrial fibrillation, congestive heart failure, valvular disease, cerebrovascular disease and those with a BMI over 30 kg/m 2 , most of which were not excluded in most studies.…”
Section: Discussionmentioning
confidence: 99%